Cataract prevalence and prevention in Europe: a literature review. (20th June 2012) - Prokofyeva, Elena; Wegener, Alfred; Zrenner, Eberhart
Abstract: This literature review is aimed at the evaluation of the potential for cataract prevention in Europe. It was performed using PubMed with Mesh and free‐text terms. Studies included were (i) performed on a population of Caucasian origin at an age range of 40–95 years, (ii) cataract was clinically verified, (iii) drug record of prescriptions, their indication, a record of every diagnosis, dosage and quantity of prescribed medicine were available, (iv) sample size >300 and (v) published between 1990 and 2009. The results of 29 articles were reviewed. Former [3.75 (2.26–6.21)] or current smoking [2.34 (1.07–5.15)], diabetes of duration >10 years [2.72 (1.72–4.28)], asthma or chronic bronchitis [2.04 (1.04–3.81)], and cardiovascular disease [1.96 (1.22–3.14)] increased the risk of cataract. Cataract was more common in patients taking chlorpromazine during ≥90 days with a dosage ≥300 mg [8.8 (3.1–25.1)] and corticosteroids >5 years [3.25 (1.39–7.58)] in a daily dose >1600 mg [1.69 (1.17–2.43)]. Intake of a multivitamin/mineral formulation [2.00 (1.35–2.98)] or corticosteroids [2.12 (1.93–2.33)] also increased the risk of cataract. Corticosteroids applied orally [3.25 (1.39–7.58)], parenteral [1.56 (1.34–1.82)] or inhalational [1.58 (1.46–1.71)] lead to cataract more frequently than those applied topically: nasal [1.33 (1.21–1.45)], ear [1.31 (1.19–1.45)] or skin [1.43 (1.36–1.50)]. Outpatient cataract surgery was negatively associated with total cataract surgery costs, and chlorpromazine, corticosteroids and multivitamin/mineral formation increase the risk of posterior subcapsular cataract dependent on dose, treatment application and duration. This review presented a comprehensive overview of specific and general cataract risk factors and an update on most recent experimental studies and randomized control trials directed at cataract prevention.